Pemanfaatan Metode Scamper Dalam Pengembangan Inovasi Produk Pada Usaha: Es Teh Tali Pinggir di Jl HS Ronggo waluyo Kabupaten Karawang - Desi Jaelani; Dzakiya Rahmanita; Danang Kusnanto (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
Es Teh Tali Pinggir MSMEs in Karawang are local beverage businesses that are growing rapidly along with the increasing public demand for ready-to-drink beverage products. However, the dynamics of competition between businesses that offer similar products require continuous product updates. This research is directed at examining the application of the SCAMPER technique, namely Substitute, Combine, Adapt, Modify, Put to another use, Eliminate, and Reverse, as an approach in developing creativity and innovation in Tali Pinggir Ice Tea MSMEs. This research uses a descriptive qualitative method with data collection techniques that include observation, interviews, and documentation. The findings showed that the use of the SCAMPER technique was able to generate a variety of innovative ideas, including the replacement of ingredients to produce new flavour variants, combining tea with contemporary toppings, adjusting packaging design to make it easier to use, and utilising digital media for marketing activities. The application of this method helps MSMEs not only retain existing customers, but also attract new market segments. Thus, the SCAMPER technique has proven to be relevant in supporting innovation strategies and improving the competitiveness of MSMEs amidst the increasingly competitive beverage business.